Natural products as a source for novel antibiotics - Moloney, M (Elsevier, 2016)
Natural products have historically been of crucial importance in the identification and development of antibacterial agents. Interest in these systems has waned in recent years, but the rapid emergence of resistant bacterial strains has forced their re-evaluation as a route to identify novel chemical skeletons with antibacterial activity for elaboration in drug development. This overview examines the current situation, highlights new natural product systems which have been found, together with re-examination of some old ones, and new technologies for their identification. While natural products certainly have the potential to re-emerge as a key start-point in antibacterial drug discovery, reports of new or reinvestigated structures need to be supported with sufficient quality chemical (solubility, stability), biochemical (including toxicity in particular, along with target information) and microbiological [minimum inhibitory concentration (MIC) and resistance frequency] validation data to assist in the identification of promising hit structures and to avoid wasted effort from trawling over already cultivated territory. This is particularly important in a resource-limited research environment.